Legitimate Distinctiveness and The Entrepreneurial Identity: Influence on Investor Judgments of New Venture Plausibility - Navis, Chad; Glynn, Mary Ann (Academy of Management Review, 2011)
We theorize about how the entrepreneurial identity, which we define as the constellation of claims around the founder, new venture, and market opportunity as to “who we are” and “what we do,” serves as a touchstone for investor judgments about new venture plausibility. We propose that entrepreneurial identities are judged favorably when they are legitimately distinctive, and that such judgments are influenced by market context and are mediated by identity narratives that provide institutional primes and equivocal cues in investor sensemaking.